Neurodevelopment in patients with repaired tetralogy of Fallot - Mercer-Rosa, Laura; Favilla, Emmanuelle (Frontiers in Pediatrics, 2024)
Neurodevelopmental sequelae are prevalent and debilitating for patients with congenital heart defects. Patients born with tetralogy of Fallot (TOF) are susceptible for abnormal neurodevelopment as they have several risk factors surrounding the perinatal and perioperative period. Some risk factors have been well described in other forms of congenital heart defects, including transposition of the great arteries and single ventricle heart disease, but they have been less studied in the growing population of survivors of TOF surgery, particularly in infancy and childhood.Adolescents with TOF, even without a genetic syndrome, exhibit neuro-cognitive deficits in executive function, visual-spatial skills, memory, attention, academic achievement, social cognition, and problem-solving, to mention a few. They also have greater prevalence of anxiety disorder, disruptive behavior and attention-deficit hyperactivity disorder. These deficits impact their academic performance, social adjustment, and quality of life, thus resulting in significant stress for patients and their families. Further, they can impact their social adjustment, employment and career development as an adult.Infants and younger children can also have significant deficits in gross and fine motor skills, cognitive deficits and abnormal receptive language. Many of the risk factors associated with abnormal neurodevelopment in these patients are not readily modifiable. Therefore, patients should be referred for evaluation and early intervention to help maximize their neurodevelopment and improve overall outcomes. More study is needed to identify potentially modifiable risk factors and/or mediators of neurodevelopment, such as environmental and socio-economic factors.